The Patterns of Memorizing Qur'an for Primary School Students and the Management of Pesantren Tahfidz - Ahmad Zaenurrosyid; Abdul Kahfi; Hidayatus Sholihah (The Institute of Research and Service Community IPMAFA Pati, 2020)
Abstract The world of pesantren is an educational learning environment that effectively shapes the thinking and mentality of students effectively. Complete physical facilities such as buildings, learning environments, playgrounds or curricula and educational resources (asaatidz) that accompany 24 hours for the students intensively. The students are also protected from the temptation of contemporary social media which tends to have a negative impact during the education process on Pesantren, especially at an early age. The Madinatul Quran Islamic boarding school, which is located in Pecangaan, the South coast area in coastal Java, is interesting to be studied because the integration of this educational institution is the provision of Tahfidz Alquran for small children who are also study at formal education, Islamic primary school or state or primate primary school. This study applied the perspective of management of Islamic boarding schools by using qualitative approach. Some informants as primary data sources were the founders and administrators of Islamic boarding schools. The data was collected through in-depth interview observation methods and observations at the pesantren. Another method is the collection of documentation as a secondary data source in this Madinatul Quran Islamic boarding school. From various analyzes of the data in this study, it is found that the application of innovative methods from the teachers in the pattern of memorizing the Quran for primary school children. The two patterns of management of pesantren which are managed professionally and supported by various parties, especially on the pesantren facilities and the appreciation for human resources, the achievements of the students at the Madinatul Quran Pati Selatan pesantren.